2013
DOI: 10.1159/000350379
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-25 Induces Pulmonary Arterial Remodeling via Natural Killer T Cell-Dependent Mechanisms

Abstract: Background: Recent studies have shown that prolonged Th2-type immune inflammation in the lung induces pulmonary arterial remodeling, in part through the induction of resistin-like molecule α (RELMα) expression. However, the role of interleukin-25 (IL-25; which promotes this inflammation) in the development of the pulmonary arterial remodeling remains unknown. Methods: Ovalbumin (OVA)-sensitized C57BL/6 mice were challenged with OVA inhalation 3 times a week for 3 weeks. The effects of neutralizing anti-IL-25 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Consistently, it has been shown that IL‐25 increases endothelial cell proliferation and formation of microvessel structures, suggesting that IL‐25 may also contribute to abnormal angiogenesis, one of features of airway remodeling in asthma. In this regard, we found that injection of neutralizing anti‐IL‐25 antibody inhibits antigen‐induced pulmonary arterial wall thickening and resistin‐like molecule‐α expression in chronic asthma models . Gregory et al .…”
Section: Epithelial Cells and Their Cytokines In Allergic Airway Inflmentioning
confidence: 54%
See 1 more Smart Citation
“…Consistently, it has been shown that IL‐25 increases endothelial cell proliferation and formation of microvessel structures, suggesting that IL‐25 may also contribute to abnormal angiogenesis, one of features of airway remodeling in asthma. In this regard, we found that injection of neutralizing anti‐IL‐25 antibody inhibits antigen‐induced pulmonary arterial wall thickening and resistin‐like molecule‐α expression in chronic asthma models . Gregory et al .…”
Section: Epithelial Cells and Their Cytokines In Allergic Airway Inflmentioning
confidence: 54%
“…have shown a positive correlation between mucosal IL‐33 expression and reticular basement membrane thickness in children with severe asthma. As discussed earlier, IL‐25 also participates in airway remodeling . Relative importance of these epithelial cytokines in steroid resistance and airway remodeling in asthma in humans remains an unsolved question.…”
Section: Role Of Ilcs In Allergic Airway Inflammationmentioning
confidence: 97%
“…150,155 In addition to the induction of Th2 cytokines, one study showed that prolonged IL-17 expression in the lung induced NKT cell-dependent pulmonary arterial remodelling. 156 IL-17E also contributes to VEGF signaling-induced angiogenesis via the Erk/MAPK and PI3K/Akt pathways in asthma. 157 Moreover, blocking IL-17E in the airways of allergenFunctional mechanisms of IL-17 family cytokines X Song et al challenged mice decreases the deposition of peribronchial collagen and the hyperplasia of airway smooth muscles.…”
Section: Il-17dmentioning
confidence: 99%
“…There is ample evidence that in the lungs of mice iNKT cells carry out protective immune responses to infectious agents; some examples include the bacterium S. pneumoniae (Kinjo et al, 2011;Kawakami et al, 2003), fungi such as A. fumigatus (Albacker et al, 2013;Cohen et al, 2011), and influenza virus (De Santo et al, 2008;Ho et al, 2008). iNKT cells are also protective in diminishing lung fibrosis induced by bleomycin , but they are key participants in worsening pathogenesis in mouse models of chronic obstructive pulmonary disease Pichavant et al, 2013), models of acute lung injury (Shiga et al, 2014), ischemiareperfusion injury (Wallace et al, 2009), and lung remodeling induced in IL-25 transgenic mice (Kawashima et al, 2013).…”
Section: Inkt Cells and Lung Immunitymentioning
confidence: 99%